2020
DOI: 10.1177/0739532920968647
|View full text |Cite
|
Sign up to set email alerts
|

Accommodating interests? Elite journalism, green interest groups and the U.K. reporting of climate change

Abstract: We know that journalists accommodate green interest groups’ voices in the reporting of climate change. Argument continues, nevertheless, over the extent of groups’ contributions to coverage. The study on which this is article is based traces groups’ presence during a rapid politicization of the issue (2000–2010). Its analysis of U.K. newspaper coverage shows that groups appear alongside a growing number of political messages “to tackle” climate change and act there as a critical foil to these performances and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Framing as a concept originated from Goffman (1974), who understood its importance when organizing ideas to help audiences interpret how to perceive and respond to issues and events presented to them in the news (Entman, 1993; Scheufele, 2004). With this as context, numerous studies have examined the news media’s use of framing and how it contributes to one’s perceptions and willingness to take action on politically charged issues like climate change (Benford & Snow, 2000; Matthews, 2020; Nisbet, 2009). The outcome of several framing studies has shown that the American news framing of the climate crisis has had considerable influence on the public’s understanding of climate-related issues, but there is a lack of public engagement (Feldman & Hart, 2018a; Geiger et al, 2017; Nabi et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Framing as a concept originated from Goffman (1974), who understood its importance when organizing ideas to help audiences interpret how to perceive and respond to issues and events presented to them in the news (Entman, 1993; Scheufele, 2004). With this as context, numerous studies have examined the news media’s use of framing and how it contributes to one’s perceptions and willingness to take action on politically charged issues like climate change (Benford & Snow, 2000; Matthews, 2020; Nisbet, 2009). The outcome of several framing studies has shown that the American news framing of the climate crisis has had considerable influence on the public’s understanding of climate-related issues, but there is a lack of public engagement (Feldman & Hart, 2018a; Geiger et al, 2017; Nabi et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, when news stories report on mitigation behaviors, they focus on individual behaviors like purchasing energy-efficient appliances and products, recycling, less meat consumption and other lifestyle choices (Feldman & Hart, 2018b; Geiger et al, 2017; Tschötschel et al, 2020). However, this strategy has been unsuccessful in influencing people to take action because the burden is on the individual to change and ignores how businesses and governments must change (Barnosky et al, 2016; Matthews, 2020; Seelig, 2019). For example, there is no mention regarding how a policy may regulate power plants’ greenhouse gas emissions or other pollutants or the benefits of a carbon tax and investment in renewable energies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since strategic actors aim to influence journalistic sense-making (Boyle & Mower, 2018), the process of building a media frame lies on a “continuum between frame setting and frame sending” (Brüggemann, 2014, p. 64). At the same time, news media tend to reflect the perspectives of those who hold dominant positions in society, such as politicians, ambassadors and business leaders (e.g., Corcoran & Fahy, 2009; Matthews, 2020), who aim to “push their views in a way that forges the audience’s perceptions and responsibility assignments of social problems” (Chang & Lee, 2020, p. 94). Accordingly, this study highlights a complicated frame-building process, which manifests itself through the delicate tensions between various agents.…”
Section: Framing In a National And Global Contextmentioning
confidence: 99%
“…In this study, the focus is on three key agents: the UN as a strategic actor trying to influence the framing of local media to forge a desired audience perceptions on refugee-related issues around WRD; local social elites, who persistently try to shape public perceptions about refugees and migrants (Corcoran & Fahy, 2009; Matthews, 2020); and, last but not least, local newspapers, which serve as the conduits of the narrative and are influenced by external social structures as well as internal professional constraints. To highlight the tensions inherent in framing forced migration, we focus on “global journalism”—a unique form of journalistic storytelling, which blurs traditional boundaries between domestic and foreign news and provides a cosmopolitan viewpoint on global issues (Berglez, 2008; van Leuven & Berglez, 2016).…”
Section: Framing In a National And Global Contextmentioning
confidence: 99%
See 1 more Smart Citation